In Pursuit of Authenticity: Induced Pluripotent Stem Cell-Derived Retinal Pigment Epithelium for Clinical Applications. (11th July 2016) - Miyagishima, Kiyoharu J.; Wan, Qin; Corneo, Barbara; Sharma, Ruchi; Lotfi, Mostafa R.; Boles, Nathan C.; Hua, Fang; Maminishkis, Arvydas; Zhang, Congxiao; Blenkinsop, Timothy; Khristov, Vladimir; Jha, Balendu S.; et al.
Abstract : For effective treatment, induced pluripotent stem cell (iPSC)-retinal pigment epithelium (RPE) must recapitulate the physiology of native human RPE cells. A set of physiologically relevant functional assays that assess the polarized functional activity and maturation state of the intact RPE monolayer is provided. The study data show that donor-to-donor variability exceeds the tissue-to-tissue variability for a given donor and provides, for the first time, criteria necessary to identify iPSC-RPE cells most suitable for clinical application. Abstract: Induced pluripotent stem cells (iPSCs) can be efficiently differentiated into retinal pigment epithelium (RPE), offering the possibility of autologous cell replacement therapy for retinal degeneration stemming from RPE loss. The generation and maintenance of epithelial apical-basolateral polarity is fundamental for iPSC-derived RPE (iPSC-RPE) to recapitulate native RPE structure and function. Presently, no criteria have been established to determine clonal or donor based heterogeneity in the polarization and maturation state of iPSC-RPE. We provide an unbiased structural, molecular, and physiological evaluation of 15 iPSC-RPE that have been derived from distinct tissues from several different donors. We assessed the intact RPE monolayer in terms of an ATP-dependent signaling pathway that drives critical aspects of RPE function, including calcium and electrophysiological responses, as well as steady-state fluid transport. These responses have key in vivo counterparts that together help determine the homeostasis of the distal retina. We characterized the donor and clonal variation and found that iPSC-RPE function was more significantly affected by the genetic differences between different donors than the epigenetic differences associated with different starting tissues. This study provides a reference dataset to authenticate genetically diverse iPSC-RPE derived for clinical applications. Significance: The retinal pigment epithelium (RPE) is essential for maintaining visual function. RPE derived from human induced pluripotent stem cells (iPSC-RPE) offer a promising cell-based transplantation therapy for slowing or rescuing RPE-induced visual function loss. For effective treatment, iPSC-RPE must recapitulate the physiology of native human RPE. A set of physiologically relevant functional assays are provided that assess the polarized functional activity and maturation state of the intact RPE monolayer. The present data show that donor-to-donor variability exceeds the tissue-to-tissue variability for a given donor and provides, for the first time, criteria necessary to identify iPSC-RPE most suitable for clinical application.